Condições bacteriológicas da superfície das poltronas hematológicas par hemodiálise - Ferreira, Natália Cristina [UNESP] (2014)
Health facilities and inanimate surfaces surrounding the patient keep close relation with infections related to care and health, with important centers of contact and transmission of pathogens and can be transferred to many different surfaces through direct and indirect contact. There are numerous studies that show that the hospital items can become vehicles of dissemination, compromising patient safety. Faced with this problem, this study aimed to analyze the bacteriological conditions in the surface of hematologic arm for hemodialysis. After approval by the Research Ethics Committee of the randomization arm, double- blind trial was performed and started sampling the four chair the seven procedures in five different locations in the chair. The product used for routine cleaning of the unit was 70% alcohol with hospital pad composed of 100% cotton in size 30 x 30cm, moistened with 40 ml of 70% ethanol. Bacteriological sampling was used to ensure fenestrated sterile field in the same site collection using Swab. The swab was transported to the laboratory in culture medium gel Stuart for identification. After testing, was performed antibiogram of isolates and sensitivity test in vitro using Kirby and Bauer method with modifications as described by Cooke (1988). For in vitro test used three disinfectants front seats of the isolated bacteria that are considered of great importance in the control of hospital infection. The result demonstrated that the largest colony-forming unit was compared to Staphylococcus sp, followed by Gram-positive bacillus, Staphylococcus aureus, Pseudomonas, Enterobacter cloacae, and Acinetobacter, predominantly Staphylococcus sp on all surfaces of the chair, with predominance in the left arm armchair coinciding with the arm of the patient who has an arteriovenous fistula (70%). Regarding sensitivity, Acinetobacter were sensitive to all antibiotics tested, whereas Pseudomonas were sensitive to sulfa / trimethoprim, ...